Establish eaudiobook - Peed, Matthew (Dungeon Robotics, 2019)
Regan Earle was a robotics scientist that inadvertently caused the robot takeover of the world. When his last creation completes a decade long plan to end his own life, he ends up surprised. Creation offers him a second chance to test his wits and cunning in another world. Fate, however, is fickle and Regan ends up as a Dungeon Core . . . with ALL his memories. Is the world of Murgin ready to face such a dungeon? Let's find out . . . Earth 2150. Nearly twenty years since the robot uprising, where all AIs designed by inventor Dr. Regan Earle went rogue and started to take over the world. Or at least, that's what everyone thought until a year later Earle himself sent out a message. A message that stated his creations would shut down if he were killed. He even went so far as to place a beacon on top of his building that broadcasted his location. The humans fought against the machines for decades in a futile attempt to destroy the tower. Until one day . . .